Australian Identity Politics Playing Tricks for Young South Sudanese Australians. (3rd September 2022) - Williams, Sarah
ABSTRACT: This article explores the key themes of African diaspora life for young people in Australia and their interplay with identity politics, primarily focusing on young South Sudanese Australians. This is captured through their participation in youth participatory action research (YPAR) facilitated by a small non-profit, Footprints . The notion of 'identity politics playing tricks' was derived from observing Footprints YPAR projects as South Sudanese Australian (SSA) Hip Hop artists discern their diaspora identities in the backdrop of a nation that often displays a political agenda about their presence. Alternatively, young people re-frame and assert their identity formation through their Blackness and pride in culture and establish themselves as social agents in the world. Utilising 'critical race theories' through the lens of 'urban youth culture', this article demonstrates how participants examine their multifaceted experiences whilst navigating cultural codes; how they negotiate and articulate their own identities in challenging circumstances and seeks to understand communities' views on diaspora, social, national and cultural identities' in a diverse environment. It addressed the themes of the politics of 'reclaiming identity'. Findings point to the necessity to further explore racialisation discourses in localised contexts whilst prioritising the self-articulation of identities reviewing how young people enact agency and resilience.